Driving Brand Success through Sports Sponsorship: Strategic Insights, Challenges, and Opportunities in Emerging Markets - Tinaz, Cem (ASEAN Journal of Sport for Development and Peace, 2024)
Traditional methods of sports sponsorship have given way to more complex, multidimensional approaches that take advantage of media attention and appeal to the emotional bond that exists between sports and fans. Nevertheless, most previous research has concentrated on developed markets, leaving a knowledge vacuum regarding sponsorship in emerging nations. To close this gap, this study examines sponsorship management from the viewpoints of agencies, sponsees, and sponsors involved in the Turkish sports industry. The study examines how businesses can use sports sponsorship as a strategic marketing tool to increase consumer engagement, brand awareness, and visibility. Important background elements like unstable economies, underdeveloped sports infrastructures, and government intervention are discussed, along with the sponsorship opportunities and challenges they pose. Utilising a qualitative methodology, the study conducts in-depth interviews with significant stakeholders to examine decision-making procedures, crucial success elements, and the quantifiable influence of sponsorships. The results indicate that improving sponsorship effectiveness requires long-term partnerships, stakeholder alignment, and digital engagement. The study adds to the body of knowledge on sponsorship by providing insights into the intricate dynamics of sponsorship management in emerging markets, where political involvement and economic volatility play critical roles.